2022
DOI: 10.11149/jkaoh.2022.46.2.78
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of dental treatments among the disabled in a charity dental clinic, Cheongju city

Abstract: Objectives: Disabled people experience difficulties in accessing dental services. Some of them tend to rely on charity dental services due to financial reasons. The purpose of this study is to identify some of the treatment statuses of disabled people to aid in planning oral health policies. Methods: This study analyzed the dental records of 141 patients from 2014 to 2019 in a charity dental clinic in Cheongju City. The demographic characteristics such as gender, age, area, social security, and type of disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The high clinical efficacy of digital methods requires economists, researchers, and specialists in the field of healthcare organizations to analyze the economic efficiency of the production process digitalization in the trajectory of economic development of a CDC [10,11], which will provide the managerial decision-maker with scientifically based information about the necessary material costs for the purchase of necessary equipment (3D printers, milling machines, and other dental instruments and equipment) [12], and capital investment in the creation of a CDO and ensuring the necessary trajectory of its economic development. Another significant trend in the research is the factor analysis of CDO costs and the development of effective models for the process management of CDO financial flows using the achievements of modern economic science and mathematical programming methods [13].…”
Section: Introductionmentioning
confidence: 99%
“…The high clinical efficacy of digital methods requires economists, researchers, and specialists in the field of healthcare organizations to analyze the economic efficiency of the production process digitalization in the trajectory of economic development of a CDC [10,11], which will provide the managerial decision-maker with scientifically based information about the necessary material costs for the purchase of necessary equipment (3D printers, milling machines, and other dental instruments and equipment) [12], and capital investment in the creation of a CDO and ensuring the necessary trajectory of its economic development. Another significant trend in the research is the factor analysis of CDO costs and the development of effective models for the process management of CDO financial flows using the achievements of modern economic science and mathematical programming methods [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that the rate of unmet dental treatment is still high among some individuals with disabilities with periodontal disease and dental caries 14) . In addition, the status of dental caries among disabled children and adolescents 15) , oral health status of people with disabilities in certain regions 16,17) , dental care utilization by them 18,19) , and inadequate oral healthcare systems 20) have been reported. However, most studies have reported cross-sectional results, and there is a lack of information regarding the factors influencing tooth loss, which represents the ultimate outcome of oral health based on long-term follow-up results.…”
Section: Introductionmentioning
confidence: 99%